Structural, electronic, and electrocatalytic evaluation of spinel transition metal sulfide supported reduced graphene oxide. Issue 4 (10th January 2022) - Santhosh Kumar, Ramasamy; Ramakrishnan, Shanmugam; Prabhakaran, Sampath; Kim, Ae Rhan; Kumar, Dharman Ranjith; Kim, Do Hwan; Yoo, Dong Jin
Abstract : Highly active and durable hierarchical structure of ZnCo2 S4 grown on reduced graphene oxide nanosheet electrocatalysts for the green production of hydrogen gas via water electrolysis. Abstract : Development of highly active and durable non-precious spinel transition metal sulfide (STMS)-based electrocatalysts plays a vital role in increasing the efficiency of hydrogen production via water electrolysis. Herein, we have synthesized a hierarchical nanostructured ZnCo2 S4 on reduced graphene oxide (ZCS@rGO) sheet using a cost-effective hydrothermal synthesis method. The prepared ZCS@rGO shows improved hydrogen desorption and adsorption energy of the electrocatalyst surface towards efficient hydrogen evolution reaction (HER). As a result, ZCS@rGO showed lower HER overpotential ( η 10 = 135 eV) and Tafel slope (47 mV dec −1 ) and superior durability at 10 mA cm −2 for 36 h, as compared to the benchmark catalyst of Pt–C. Further, the electronic structure and HER mechanism of the ZCS@rGO catalyst were investigated by density functional theory calculations. This work provides a new pathway for the rational design of highly active and durable non-precious STMS-based electrocatalysts for hydrogen production.